Social Support and Resilience in Student: How the role of Hope as a Mediator Variable? - Faizah Oktaviani; Muhammad Farid; Isrida Yul Arifiana (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to prove the relationship between social support and resilience in student with hope as a mediator variable. The research subjects consisted of 185 students at Al-Ishlah Islamic Boarding School, Paciran, Lamongan. Research measuring instruments include a resilience scale, a social support scale, and The Indonesian Hope Scale (IHS). The data in this study were analyzed using path analysis test. The results prove that there is a significant and positive relationship between social support and resilience with hope as a mediator variable. The percentage of the mediating effect of hope is 68.4% in the relationship between social support and resilience. High social support will increase hope which in turn can increase resilience in students. The implication of this study for students is that it can provide awareness that establishing social relationships with people around and having hope for the future is very important to help them overcome pressures and challenges while living in boarding schools.